BANKRUPTCY PREDICTION OF LISTED CEMENT COMPANY IN INDONESIAN STOCK EXCHANGES USING ALTMAN Z-SCORE MODEL - Arifia Fitriani; Alizar Hasan; Ahmad syafruddin Indrapriyatna (Spektrum Industri, 2019)
Ratio analysis is one of the most competent tools to predictthe bankruptcy of a company. In this paper the bankruptcyprediction of listed cement company in Indonesian StockExchanges has been evaluated using Altman Z-score. Thisstudy aims to determine the level of the bankruptcy of thelisted cement companies in the Indonesian Stock Exchangeduring 2013 to 2017. There are four listed cementcompanies, namely PT Semen A, PT Semen B, PT Semen Cand PT Semen D. Based on the results of the research, itshows that PT Semen A, PT Semen B and PT Semen C are inthe safe zone with the highest Z value which is 15,822 andthe lowest Z value which is 3,542. PT Semen D is in thebankrupt zone because it has a Z value below 1.8. For thatreason, all companies need to improve the performanceimmediately to avoid the bankruptcy happening. There aremany ways to avoid the bankruptcy such as improving thesales revenue, improving operational cost and wastereduction in operation.